Endophytic fungi associated with Vitis vinifera with antibiosis capacity against Botrytis cinerea - León-Ttacca, Betsabé (2024)
Introduction. Endophytic fungi (EF) in grapevines (Vitis vinifera) have great potential for agricultural applications and may represent possible biological control agents for vineyards. Objective. To isolate and identify endophytic fungi (EF) from grapevine plants with antibiosis capacity against Botrytis cinerea. Materials and methods. Young and mature branches from forty healthy grapevine plants were collected from seven production lots in the Cañete province, Lima, Peru, during March to May 2022. EF isolation was performed on 702 sections of disinfected tissues using potato dextrose agar (PDA) culture medium, and identification was carried out at the genus level. Secondary metabolites were extracted from twenty-eight EF strains to determine the mycelial inhibition of the pathogen. An analysis of variance (ANOVA) was conducted on the evaluated parameters using the Minitab statistical program. Results. A total of 129 EF strains were isolated from leaves and stems of young and mature grapevine branches, encompassing seven genera (Trichoderma, Aspergillus, Alternaria, Cladosporium, Fusarium, Nigrospora, and Stemphylium). The highest frequency was found in leaves and mature branches. Trichoderma and Alternaria were the most frecuent genera in grapevine plants, with 22.48 % and 21.71%, respectively. Metabolites obtained from the EFVH-01 strain of the genus Cladosporium, and EF-99 and EF-70 strains of the genus Alternaria, had the greatest effect on mycelial inhibition of the pathogen. Conclusions. Strains of endophytic fungi from the genera Cladosporium and Alternaria showed antibiosis capacity against Botrytis cinerea at the laboratory scale, which could potential biocontrol agents of pathogens in grapevine cultivation.